1999
DOI: 10.2108/zsj.16.71
|View full text |Cite
|
Sign up to set email alerts
|

The Air-puff Evoked Escape Behavior of the Cricket Gryllus bimaculatus and its Compensational Recovery after Cercal Ablations

Abstract: The air-puff evoked escape behavior of the cricket, Gryllus bimaculatus, was investigated. Crickets almost always escaped away from the stimulus source. In an optimal condition, the mean escape direction was 162° opposite to the stimulus source. Stronger (higher velocity) air-puff elicited an escape in larger number of crickets. However, the escape direction became incorrect when the stimulus was too strong.Crickets with bilateral cercal ablation did not show any escape to an air-puff, while unilaterally ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 37 publications
4
72
2
2
Order By: Relevance
“…These velocities appear to be too high compared to that generated by an approaching predator Magal et al, 2006). Moreover, a stimulation of 90 cm/s induces a low response in the crickets as only 1.3% and 10% of the crickets reacted respectively (Kanou et al, 1999(Kanou et al, , 2006, whereas in our experiments 43% of the adult crickets (and 80% of J1) responded to a stimulation of 25 cm/ s.…”
Section: Tablecontrasting
confidence: 73%
See 4 more Smart Citations
“…These velocities appear to be too high compared to that generated by an approaching predator Magal et al, 2006). Moreover, a stimulation of 90 cm/s induces a low response in the crickets as only 1.3% and 10% of the crickets reacted respectively (Kanou et al, 1999(Kanou et al, , 2006, whereas in our experiments 43% of the adult crickets (and 80% of J1) responded to a stimulation of 25 cm/ s.…”
Section: Tablecontrasting
confidence: 73%
“…It has been reported that Troglophilus neglectus crickets use a different sequence of movements to escape: they jump backward, away from the stimulus (Schrader, 2000), which could constitute a better strategy to quickly create distance between the cricket and objects approaching from any direction. The ability to detect approaching objects was higher in our experiments than that observed in Gryllus bimaculatus (Kanou et al, 1999), or in Gryllodes sigillatus (Kanou et al, 2006). Our study was conducted using a piston approaching at 25 cm/s, a speed that seems to evoke the highest escape response of N. sylvestris (Dangles et al, 2006b).…”
Section: Tablementioning
confidence: 56%
See 3 more Smart Citations